THE TERM SOCIAL ILLUSIONS IN COLLEGES AND SCIENTIFIC DISCOURSE - Матвіїшин, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article states the origin, content, functions, types and mechanisms of social illusions of personality in terms of various socio-humanitarian sciences. Advocates psychodynamic and cognitive approaches to designing social illusions during personohenezu.